Evaluating life cycle cost (LCC) and performance between cold in place recycling (CIPR) and reconstruction method - Wan Imran bin Wan Omar (Kulliyyah of Architecture and Environmental Design, International Islamic University Malaysia, 2015)
Pavement management is a very important subject that demands proper planning and implementation. The maintenance of a road pavement throughout its life cycle had to be carried out timely using the most economical method. However, rapid road deterioration and eventual failure from both climatic and vehicle loads impacts have significantly incurred the total cost of road maintenance works. In the maintenance of road pavement rehabilitation, alternatives method to reconstruction method that called cold-in place recycling (CIPR) which has been employed in many countries worldwide, including Malaysia to overcome the quality of road. In this case study, a comparative performance and life cycle costs analysis of CIPR versus reconstruction method is established. The actual functional and structural performances of both alternatives are measured and compared against the prediction using the performance condition index (PCI). In addition, the life cycle cost (LCC) for the two alternatives are performed and compared, taking into consideration of the net present value (NPV) in the calculation. LCC is the most cost effective approach so that the least long term cost of ownership is achieve. LCC is a process of evaluating the economic performance of the roads over its entire life. Lastly, the performance and cost analysis for each method are integrated to provide a composite view of the correlation between the two major elements. It is found that even though the CIPR is slightly more expansive than the conventional method, but its performance is substantially superior. The study indicates that CIPR can be considered as the more optimum method of pavement rehabilitation between the two alternatives. In conclusion, we can say that although CIPR incurred a higher initial cost but with its better performance, future maintenance cost is become lower than reconstruction method.